Validity of the SARC-F questionnaire in assessing sarcopenia in patients with chronic kidney disease: a cross-sectional study - Du, Wen; Gao, Chenni; Wang, Xuejie; Ma, Xiaobo; Xie, Jingyuan; Yu, Haijin; Yang, Zhenhua; Chen, Zijin; Chen, Xiaonong (Frontiers in Medicine, 2023)
Objective: To examine the validity of the 5-component SARC-F questionnaire for screening sarcopenia among patients with chronic kidney disease (CKD). Methods: Eligible participants were enrolled from the Department of Nephrology, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine from March 2019 to November 2019. Evaluations were performed using the self-administered SARC-F questionnaire. Sarcopenia was diagnosed by grip strength, the chair stand test and appendicular skeletal muscle mass. The severity of sarcopenia was evaluated by gait speed. We calculated the sensitivity and specificity of the SARC-F to evaluate construct validity. Moreover, receiver operating characteristic (ROC) curve analysis was performed to identify the cutoff value for nondialysis-dependent (NDD) CKD patients’ and maintenance hemodialysis (MHD) patients’ scores. Results: A total of 105 NDD-CKD patients and 125 MHD patients were included, and the prevalence of sarcopenia was 5.7% and 31.2%, respectively. Among them, there were 21 (16.8%) MHD patients with severe sarcopenia but no NDD-CKD patients with severe sarcopenia. The sensitivity and specificity of the SARC-F were 16.7% and 98% for NDD-CKD patients, and 48.7% and 89.5% for MHD patients, respectively. For NDD-CKD patients, the area under the receiver operating characteristic curve (AUROC) of the total SARC-F score was 0.978 (95% confidence interval (CI): 0.929-0.997, P<0.001), and the cutoff value of 1 reached the highest Youden index of 0.950 and max ROC curve area of 0.974. For MHD patients, the AUROC of the total SARC-F score was 0.730 (95% CI: 0.644-0.806, P<0.001), and the cutoff value of 4 reached the highest Youden index of 0.383 and max ROC curve area of 0.691. Conclusions: CKD patients, especially MHD patients, were at high risk of suffering sarcopenia. The SARC-F had low-to-moderate sensitivity but high specificity for screening sarcopenia among patients with CKD. The best cutoff values of the SARC-F score were different for screening sarcopenia among NDD-CKD and MHD patients.